2015
DOI: 10.1152/ajpregu.00073.2015
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin: the missing link for preeclampsia?

Abstract: eclampsia is a devastating cardiovascular disorder of late pregnancy, affecting 5-7% of all pregnancies and claiming the lives of 76,000 mothers and 500,000 children each year. Various lines of evidence support a "tissue rejection" type reaction toward the placenta as the primary initiating event in the development of preeclampsia, followed by a complex interplay among immune, vascular, renal, and angiogenic mechanisms that have been implicated in the pathogenesis of preeclampsia beginning around the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…Numerous pathways have been proposed to have key roles in inducing placental disease, including deficient heme oxygenase expression, placental hypoxia, genetic factors, corin deficiency, autoantibodies against the angiotensin receptor, oxidative stress, inflammation, altered natural killer cell signaling, deficient catechol-O-methyl transferase, complement activation, and more recently aberrant vasopressin production. 11,[55][56][57][58][59][60][61][62] Interestingly, several of these pathways were shown to increase placental production of the antiangiogenic factors in cell culture or animal models. However, human studies describing the temporal relationship between the angiogenic factors and the upstream pathways are still lacking before one can draw definitive conclusions.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
“…Numerous pathways have been proposed to have key roles in inducing placental disease, including deficient heme oxygenase expression, placental hypoxia, genetic factors, corin deficiency, autoantibodies against the angiotensin receptor, oxidative stress, inflammation, altered natural killer cell signaling, deficient catechol-O-methyl transferase, complement activation, and more recently aberrant vasopressin production. 11,[55][56][57][58][59][60][61][62] Interestingly, several of these pathways were shown to increase placental production of the antiangiogenic factors in cell culture or animal models. However, human studies describing the temporal relationship between the angiogenic factors and the upstream pathways are still lacking before one can draw definitive conclusions.…”
Section: Biology Of Antiangiogenic State In Preeclampsiamentioning
confidence: 99%
“…In addition proposing the use for plasma AVP measurements in the prediction of preeclampsia and Santillan and colleagues also hypothesized a possible involvement of AVP in the pathogenesis of preeclampsia 28,42 . They reported that chronic infusion of AVP during pregnancy in C57BL/6J mice, caused pregnancy-specific hypertension, renal glomerular endotheliosis, proteinuria, and intrauterine growth restriction.…”
Section: Biomarkers For Early Pregnancy Prediction Of Preeclampsiamentioning
confidence: 99%
“…In comparison to uncomplicated pregnancies, reduced IVCI was observed in late-onset but not in early-onset preeclampsia, suggesting a higher intravascular filling state in late-onset than in early-onset preeclampsia (Stergiotou et al 2013). Similarly, hormones regulating volume and electrolyte homeostasis such as antidiuretic hormone and natriuretic peptides are more elevated in early but not late preeclampsia (Sandgren et al 2015;Tuten et al 2015;Álvarez-Fernández et al 2016;Borges et al 2018). Decreased PV expansion in early preeclampsia may result from constitutionally low plasma volume before conception, poor expansion due to dysfunctional mechanisms of neurohormonal volume retention or extravascular leakage of intravascular fluids (Salas et al 2006;De Haas et al 2017), and is consistent with pre-existing cardiovascular dysfunction leading to chronic (type II) cardiorenal syndrome.…”
Section: Direct Cardiorenal Interactionsmentioning
confidence: 94%
“…Similarly, hormones regulating volume and electrolyte homeostasis such as antidiuretic hormone and natriuretic peptides are more elevated in early but not late preeclampsia (Sandgren et al . ; Tuten et al . ; Álvarez‐Fernández et al .…”
Section: Cardiorenal Syndromesmentioning
confidence: 99%